Effective School Leadership for Supporting Students’ Mental Health: Findings from a Narrative Literature Review - Brian P. Daly; Annie Resnikoff; Shannon Litke (Behavioral Sciences)
There is a compelling literature base in the field of education that highlights how school leaders are crucial to improving academic processes and outcomes, including instruction and raising student achievement. Research has also demonstrated that effective school leaders exhibit behaviors aligned with promoting the core issues of teaching, learning, and school improvement. Less well-known is what science says about the effectiveness of professional development and leadership preparation programs for developing the competencies needed for addressing the diverse mental health needs of students. Better understanding the science is important as school leaders are increasingly tasked with connecting leadership behaviors to students’ social and emotional outcomes, and these leaders play a large role in whether, and to what extent, mental health promotion and prevention are effectively implemented in school settings. Drawing from diverse literature bases of education and psychology, the primary objective of this narrative literature review is to determine and define effective leadership behaviors, skills, and competencies in the context of implementing school mental health programs and strategies. The secondary objective is to summarize the existing research examining leadership preparation and professional development programs that promote effective leadership practices and highlight examples of leadership programs focused on enhancing school mental health.